2021
DOI: 10.1097/tp.0000000000003368
|View full text |Cite
|
Sign up to set email alerts
|

Peritransplant Cardiometabolic and Mitochondrial Function: The Missing Piece in Donor Heart Dysfunction and Graft Failure

Abstract: Primary graft dysfunction (PGD) is an important cause of morbidity and mortality after cardiac transplantation. Donor brain stem death (BSD) is a significant contributor to donor heart dysfunction (DHD) and PGD. There remain substantial gaps in the mechanistic understanding of peritransplant cardiac dysfunction. One of these gaps is cardiac metabolism and metabolic function. The healthy heart is an 'omnivore', capable of utilising multiple sources of nutrients to fuel its enormous energetic demand. When this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 136 publications
(174 reference statements)
0
12
0
Order By: Relevance
“…In turn, sympathetic activity leads to rapid catecholamine (noradrenaline, adrenaline, and dopamine) increases in the myocardial interstitial fluid [34][35][36]. The effects of catecholamines on cardiac metabolism are numerous, including increased intracellular and mitochondrial calcium; mobilization of glycogen stores; as well as stimulation of glycolysis, beta-oxidation, and lipid accumulation, as reviewed by Wells and colleagues [37]. Importantly, adrenaline treatment before ischemia has been reported to reduce post-ischemic recovery of the rat myocardium, possibly as a result of exacerbated calcium overload [38].…”
Section: Catecholaminesmentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, sympathetic activity leads to rapid catecholamine (noradrenaline, adrenaline, and dopamine) increases in the myocardial interstitial fluid [34][35][36]. The effects of catecholamines on cardiac metabolism are numerous, including increased intracellular and mitochondrial calcium; mobilization of glycogen stores; as well as stimulation of glycolysis, beta-oxidation, and lipid accumulation, as reviewed by Wells and colleagues [37]. Importantly, adrenaline treatment before ischemia has been reported to reduce post-ischemic recovery of the rat myocardium, possibly as a result of exacerbated calcium overload [38].…”
Section: Catecholaminesmentioning
confidence: 99%
“…The catabolic pathway of BCAAs ends with the generation of acetyl-CoA and succinyl-CoA and their oxidation in the TCA cycle or anaplerosis [69]. In a healthy heart, BCAAs contribute 1-2% to the cardiac ATP production [37].…”
Section: Branched-chain Amino Acid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The United Network of Organ Sharing (UNOS) reported that 13,861 individuals in the United States became deceased donors for organ transplants in 2021, an increase for the eleventh year in a row (1). Despite being the leading resource for organs in those needing lifesaving transplants, metabolic changes that occur due to BD and in the subsequent stages of organ procurement, storage, and implantation results in inflammatory responses in the donor organs that are then "primed" for immune recognition (2)(3)(4). The interplay between immune response and organ longevity is a of long-term graft viability and success in solid organ transplantation (2,5).…”
Section: Introductionmentioning
confidence: 99%
“…6 Impaired mitochondrial function has been implicated in peritransplant cardiac dysfunction. 7 A second characteristic of TPP relevant to organ transplantation is its role as a vital coenzyme for the transketolase reaction of the pentose phosphate pathway. The pentose phosphate pathway is a major source of reduced nicotinamide adenine dinucleotide-phosphate (NADPH) for the regeneration of reduced glutathione, an important cellular antioxidant capable of inactivating reactive oxygen species that are produced by I/R which is likely involved in delayed graft function.…”
Section: Introductionmentioning
confidence: 99%